Structural changes to epitaxial (0001) holmium layers during hydrogen loading - Grier, E; Kolosov, O; Petford-Long, A; Ward, R; Wells, MR; Hjorvarsson, B (IOP, 2000)
HoHy exhibits dramatic changes in both structural and optical properties as y is varied from zero to three by hydrogen loading. This work reports on the effect of such loading upon epitaxial single-crystal Ho films grown by molecular beam epitaxy on (110) Nb∥(112̄0) Al2O3 substrates. Upon loading, the film undergoes a structural transition from hcp metal (α-phase, H in solid solution) to the fcc dihydride (β-phase). There is a further transformation between the dihydride phase and the hexagonal trihydride (γ-phase). Three films of HoHy, where, nominally, y = 0, 2, 3, were studied by XRD, AFM, UFM, SEM and TEM. Triangular networks of features of width approximately 300 nm and height approximately 20-30 nm that align with the [01̄1], [1̄01] and [11̄0] directions of the dihydride sample are seen on the surface of both the dihydride and the trihydride samples, but have a much greater density on the surface of the latter. Such features are not present on the as-grown metal layer. In situ controlled-environment transmission electron microscopy (CETEM) studied the effects of hydrogen loading within the dihydride phase, in cross sectional geometry. During loading, slip within the dihydride phase was observed. The hypothesis that the triangular features are due to the precipitation of the di- and trihydride compounds, with expanded lattices, on the slip planes within the α- or β-phase host crystal is discussed.